SYSTEM OF SUBJECTS OF ENSURING LEGALITY DURING THE ADMINISTRATION OF JUSTICE (Bulletin of criminological association of Ukraine, 2023)
The article, based on the analysis of the scientific views of scientists and the norms of current legislation, identifies a range of key subjects of ensuring legality during the administration of justice. It is argued that each of the specified subjects has its own, special administrative and legal status. The author's vision of the classification of subjects of ensuring legality during the administration of justice is proposed. Ensuring legality during the administration of justice is a set of interrelated elements that, in interaction with each other, form a holistic complex mechanism. One of the key elements in the studied context are the subjects of such activities. At the same time, each of the specified subjects has its own, special administrative and legal status. A rather diverse range of subjects is noted that directly or indirectly contribute to ensuring legality during the administration of justice. The latter are proposed to be divided into groups using various differentiation criteria, in particular, 1) by subject composition: a) individual (judges, individual representatives of the public, participants in the trial (plaintiff, defendant, defendant, victim, witness, etc.), interested in observing the law); b) collective (in particular, the Supreme Court of Justice); 2) by their relationship to the act of justice, they are divided into those whose actions are performed during the act of justice itself, and those who have an indirect influence on it (for example, through the formation of the personnel of the courts); 3) by the features of the administrative and legal status, it is advisable to distinguish: firstly, those directly responsible for ensuring legality during the administration of justice (first instance judges); secondly, subjects who verify compliance with the requirements of the legality of court decisions as acts of justice (judges of the appellate and cassation instances); thirdly, entities that promote the independence of judges in the administration of justice in order to ensure legality, including on the basis of adequate staffing (judicial governance and self-government bodies); fourthly, state authorities that shape the content of legality, primarily the Verkhovna Rada as the sole legislative body.
Keywords: subject; justice; legality; administrative and legal status